Metformin increases survival in hypopharyngeal cancer patients with diabetes mellitus: retrospective cohort study and cell-based analysis - Tsou, Yung-An; Chang, Wei-Chao; Lin, Chia-Der; Chang, Ro-Lin; Tsai, Ming-Hsui; Shih, Liang-Chun; Staniczek, Theresa; Wu, Tsu-Fang; Hsu, Hui-Ying; Chang, Wen-Dien; Lai, Chih-Ho; Chen, Chuan-Mu (Pharmaceuticals, 2021)
Hypopharyngeal squamous cell carcinoma (HSCC) is usually diagnosed at an advanced stage, leading to a poor prognosis. Even after improvement of surgical techniques, chemotherapy, and radiation technology, the survival rate of HSCC remains poor. Metformin, which is commonly used for type 2 diabetes mellitus (DM), has been suggested to reduce the risk of various cancer types. However, only a few clinical studies mentioned the relationship between metformin use and HSCC. Hence, the aim of this study was to elucidate the specific effect and mechanism of action of metformin in hypopharyngeal cancer. We first assessed whether metformin use has an effect on hypopharyngeal cancer patients with DM by conducting a retrospective cohort study. Our results showed that DM hypopharyngeal cancer patients who used metformin exhibited significantly better overall survival rates than that without metformin treatment. The cell-based analysis further indicated that metformin treatment regulated p38/JNK pathway to reduce Cyclin D1 and Bcl-2 expressions. In addition, metformin activated the pathways of AMPKα and MEK/ERK to phosphorylate p27(Thr198) and reduce mTOR phosphorylation in cells. These actions direct cells toward G1 cell cycle arrest, apoptosis, and autophagy. Our results, through combining a clinical cohort analysis with an in vitro study, demonstrate that metformin can be used for drug repositioning in the treatment of DM patients with hypopharyngeal cancer.
Gesehen am 19.07.2021